Psychopathic personality traits, suicide ideation, and suicide attempts in male prison inmates - Smith, Phillip N. (Criminal justice and behavior, 2014)
Prison inmates are at greater risk for death by suicide compared with the general population. Although many risk factors for suicide identified in the general population (e.g., depression, substance abuse) also apply to prison populations, few studies have examined variables that are of particular relevance to prison inmates. The current study used cross-sectional survey methodology to examine the relationships of primary and secondary psychopathic personality traits with current suicide ideation and previous suicide attempts in a sample of male prison inmates. Prison inmates who endorsed greater secondary psychopathic traits were more likely to be multiple-suicide attempters versus single and nonattempters. Primary psychopathic traits did not predict suicide attempt status. The relationship of secondary psychopathic traits and suicide ideation grew stronger as depressive symptoms increased. Primary psychopathic traits were not associated with increased suicide ideation either alone or in confluence with depressive symptoms.